Vaccine coverage in children, adolescents and adults with type 1 diabetes and their close contacts in Crete. Issue 11 (2nd November 2021) - Giatraki, Victoria; Dimitriou, Helen; Pappas, Aggelos; Mamoulakis, Dimitris; Makris, George; Galanakis, Emmanouil; Perdikogianni, Chrysoula
ABSTRACT: Background: Individuals with type 1 diabetes (T1D) are at increased risk of infections from vaccine-preventable diseases. This study focuses on compliance of T1D patients to the recommended vaccination schedule, vaccination of their close contacts for influenza and on factors potentially contributing to vaccination program deviations. Methods: The study population comprised children, adolescents and adults with T1D under follow-up at the Department of Pediatrics University Hospital and the Diabetic Center General Hospital, Heraklion, Crete-Greece. Data were extracted, following informed consent, from individual's vaccination booklet, medical files and telephone interview. Vaccination records, demographic parameters, glycemic control and influenza vaccination of close contacts were assessed. Results: The study included 258 participants (111 children/adolescents, 147 adults). Vaccination coverage for influenza was 76.7% for children, 64.4% for adults, for PCV 90.9% for children, but only 10.8% for the 23-valent, for hepatitis B 99% for children and 78.2% for adults. Youngsters were vaccinated against Hib 91.9%, meningococcus C 98.2%, measles-mumps-rubella 90.3%, chickenpox 86.4%, hepatitis A 76.5% and HPV 42.5%. Less than 65% of all individuals were fully vaccinated for diphtheria-tetanus-pertussis and meningococcus ACWY. Approximately 50% of the 605 close contacts were not vaccinated against influenza. Individuals with better glycemic status seemed to adhere to the recommended schedule and had a better vaccinated family environment. Conclusions: Vaccination coverage for T1D individuals was sufficient regarding the majority of routine childhood vaccines, but less for adolescence and group-specific vaccines. Their family contacts were not sufficiently vaccinated for influenza. Targeted interventions are required in order to increase vaccination rates.